2008
DOI: 10.1002/prot.22274
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the S1S2 glutamate binding domain of GLuR3

Abstract: Glutamate receptors are the most prevalent excitatory neurotransmitter receptors in the vertebrate central nervous system. Determining the structural differences between the binding sites of different subtypes is crucial to our understanding of neuronal circuits and to the development of subtype specific drugs. The structures of the binding domain (S1S2) of the GluR3 (flip) AMPA receptor subunit bound to glutamate and AMPA and the GluR2 (flop) subunit bound to glutamate were determined by X-ray crystallography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 39 publications
(81 reference statements)
5
65
0
Order By: Relevance
“…First, the significance of the lobe-locking equilibrium in the binding reaction for glutamate is evident by the much higher degree of protection of H Y450 Fig. 5A are made in this state or in S*G 2 or S*G 3 is unclear (all of the crystal structure protomers of glutamate-bound S1S2J contain these side chain interactions, whereas only some of the protomers show the interlobe main chain H-bonds) (14,27). Finally, P 0 would be associated with S*G 2 and/or S*G 3 in some way and include the H-bonds formed by H Y450 N and H G451 N .…”
Section: Discussionmentioning
confidence: 99%
“…First, the significance of the lobe-locking equilibrium in the binding reaction for glutamate is evident by the much higher degree of protection of H Y450 Fig. 5A are made in this state or in S*G 2 or S*G 3 is unclear (all of the crystal structure protomers of glutamate-bound S1S2J contain these side chain interactions, whereas only some of the protomers show the interlobe main chain H-bonds) (14,27). Finally, P 0 would be associated with S*G 2 and/or S*G 3 in some way and include the H-bonds formed by H Y450 N and H G451 N .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dynamics near the lobe interface suggest that large-scale lobe motions may be present when the LBD is bound to IW (21,23). In contrast, when the wild type LBD is bound to kainate, the lobes are in a relatively open orientation in all crystal structures to date (4,18,24,25), and this is supported by the average structure determined using NMR spectroscopy (15). The idea has been that the lobes remain separated by a steric clash between the isoprenyl group of kainate and the side chain of Leu-650 (3,18).…”
Section: Discussionmentioning
confidence: 99%
“…Although the lobes are slightly open relative to glutamate, two interlobe H-bonds (Gly-451-Gly-653 and Tyr-450-H 2 O-Ser-652) produced by a 180°rota-tion of the peptide bond are present in all three copies. These H-bonds are absent in most crystal structures of partial agonists and have been absent in all previously determined structures of kainate-bound AMPA receptors (3,18,24,25). Previous crystal structures have suggested that kainate prevents further lobe closure due to the steric clash between the side chain of Leu-650 with the isoprenyl group of kainate (foot-in-the-door mechanism) (18).…”
Section: Lobe-locking Mutations-the Ligand-binding Domain Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The structure of the nearly fulllength AMPA receptor, GluA2, has been determined (11), and structures of the extracellular domains of all three subtypes have been determined (12)(13)(14)(15)(16)(17). Structures of the LBD of AMPA receptors show that full agonists bind in the cleft between two lobes, and after binding to Lobe 1, the lobes close to allow inter-* This work was supported, in whole or in part, National Institutes of Health Grant R01-GM068935 (to R. E.…”
mentioning
confidence: 99%